Media and Representation: A Criminological Analysis of Media Reports about Women Murderers in Indonesia - Wahab, Amirah Hi; Bayu, Orlen Adzano Putra (Journal of Feminism and Gender Studies, 2025)
A Women are constructed by the patriarchal society as weak and gentle, loving, forgiving, polite and well-mannered. Which is then passed down into a patriarchal culture, patriarchal culture makes men in a dominant position towards the community environment, and women only submit to listening and following orders. Patriarchal culture in practice constructs a perspective or thought and view that women are just an object (property) to be owned. In the tightness felt by women with feelings of being marginalized by a society that contributes to patriarchal practices, it implies that women find it difficult to move out of the domestic space into a wider public space. The media becomes one of the agents that carry values and norms that implement the practice of marginalizing women. This article will discuss the framing and construction of the media embedded in female murderers in Indonesia, which is part of the media's representation of women as perpetrators of murder. This research also reviews from a criminological aspect. The method used is a qualitative approach with text analysis method and data management in the form of document study and text observation.